Ausländische Legitimation für den Reichsbischof? Die mißlungenen Versuche, durch britische oder skandinavische Teilnahme an der Einführung des Reichsbischofs der deutschen Kirchenleitung internationale Anerkennung zu verschaffen - Jarlert, Anders (Kirchliche Zeitgeschichte, 1995)
The unsuccessful attempts made to obtain a British or Nordic representation on the occasion of the installation of the German Reich Bishop in 1933, and thereby to obtain some form of international recognition for the German church leadership, reveal all too clearly the combination of church-political naivete and activity amongst certain leading figures in both the British and Swedish churches, and their sympathies for the Third Reich. In the first round, these moves were prevented by co-operation amongst the nordic church authorities and their English counterparts. In the second round, the last attempt was blocked by the intervention of the Swedish government, which showed that the question was regarded as not merely an internal ecclesiastical affair. In the politically delicate situation of the 1930s and 1940s, inter-church relations also had international dimensions, and consequently the churches' freedom to conduct their own affairs, even in those states outside any existing alliances, were strictly limited.